Implementasi Pembelajaran Kooperatif Tipe Student Teams Achievement Divisions pada Mata Pelajaran Fiqih dalam Meningkatkan Pemahaman Belajar Siswa - Asiyah, Asiyah; Marfianto, Tri; Rulyanti, Elmy; Sahudin, Sahudin (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2023)
The cooperative learning model is a form of learning based on a constructivist approach which refers to learning methods. One type of learning model that is relevant, effective and efficient for the purposes of learning fiqh, especially lending and borrowing material, is the Student Teams Achievement Division (STAD) type cooperative model. The advantage of STAD learning is that it can combine academic competence (learning to know, learning to do, learning to be) with social competence (learning to live together). This research aims to analyze the application of STAD learning in improving students' understanding of learning. The results of the research show that in the STAD type cooperative method, students are required to look for the material assigned in the group and they are more courageous in expressing opinions and ideas that are in the minds of the group members. As a result, students are more critical in the social environment and are braver and more active in front of the class. The application of the STAD type cooperative method in learning activities in fiqh subjects to improve students' learning understanding is quite interesting to research. Therefore, we hope that there will be further researchers regarding this matter in the future